2015
DOI: 10.1155/2015/932161
|View full text |Cite
|
Sign up to set email alerts
|

Gene Delivery into Plant Cells for Recombinant Protein Production

Abstract: Recombinant proteins are primarily produced from cultures of mammalian, insect, and bacteria cells. In recent years, the development of deconstructed virus-based vectors has allowed plants to become a viable platform for recombinant protein production, with advantages in versatility, speed, cost, scalability, and safety over the current production paradigms. In this paper, we review the recent progress in the methodology of agroinfiltration, a solution to overcome the challenge of transgene delivery into plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 57 publications
(110 reference statements)
1
57
0
1
Order By: Relevance
“…In addition, transient expression is genome integration-independent strategy, which will not be affected by position effects existing in stable transformation, once that the expression vector remains an episomal DNA molecule [22]. Our result is in accordance with previous works, which indicated that agroinfiltration could efficiently resulted in transferring of Agrobacterium into the plant leaves and robust expression of recombinant proteins [24,[52][53][54]. In our study, the infiltration of agrobacterium into the intercellular space of the leaf was performed with syringe method (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, transient expression is genome integration-independent strategy, which will not be affected by position effects existing in stable transformation, once that the expression vector remains an episomal DNA molecule [22]. Our result is in accordance with previous works, which indicated that agroinfiltration could efficiently resulted in transferring of Agrobacterium into the plant leaves and robust expression of recombinant proteins [24,[52][53][54]. In our study, the infiltration of agrobacterium into the intercellular space of the leaf was performed with syringe method (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, lower induction of the immune system and no limitation in terms of the size of transgenic DNA add versatility to this system. In addition to its speed and high yield, the transient expression platform presents versatility in terms of the expression and accumulation of personalized recombinant proteins, including therapeutics for patient-specific cancers and vaccines for viruses that show rapid antigenic drift and/or multiple strains with unpredictable outbreaks [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The peak protein expression is typically observed in less than 7 days postinfiltration which is significantly faster when compared to the full virus strategy which requires more than 2 weeks in order to generate a systemic infection for expression. The promise of this platform has been evidenced in numerous successful clinical trials, which demonstrated safety and efficacy of plant-made protein therapeutics and biologics [11 ]. For example, in responding to the H1N1 influenza virus pandemic that occurred in 2009, Medicago, a Canadian company, reported producing the vaccine candidate, hemagglutinin in 19 days in Nicotiana benthamiana [10].…”
Section: Transient Expression In Plantsmentioning
confidence: 99%
“…Plant transient expression can be used to produce vaccines at low cost on an agricultural scale and with a low risk of contamination of the product with animal pathogens as reviewed in (Chen & Lai 2015). Furthermore, plant-based vaccines have been proposed as a new approach for oral delivery such as expression of recombinant protein in edible plants like corn and rice (Kapila et al 1997;Nochi et al 2007;Shoji et al 2011).…”
Section: Introductionmentioning
confidence: 99%